The image of COVID-19 in the Serbian daily newspapers - Jevtović, Zoran B.; Bajić, Predrag Đ. (Sociološki pregled, 2020)
This work is focused on reporting of daily newspapers in Serbia during coronavirus (COVID-19) pandemic, and specifics of dominant narratives and relationship between the government and popular press. The content research includes the first half of 2020, when 1,271 from eight influential daily papers were analysed. While the representatives of the quality press have tried to steer the attention of citizens and introduce serious questions most tabloids trivialised the danger as another spectacle which will secure larger sales irrespective of social consequences and ethical norms of journalistic profession. Objectivity and unbiasedness are sacrificed for sensationalism, spectacle and political clientelism. Celebritization of medical profession has only led to spread of confusion in public opinion, while revealing how political elites eagerly use crisis for promotion of their own ideas and programs, instead of professional debate.
Keywords: COVID-19; daily newspapers; tabloidization; moral panic; political clientelism